2019
DOI: 10.1007/s11418-019-01372-x
|View full text |Cite|
|
Sign up to set email alerts
|

Gingerol inhibits cisplatin-induced acute and delayed emesis in rats and minks by regulating the central and peripheral 5-HT, SP, and DA systems

Abstract: Gingerol, a biologically active component in ginger, has shown antiemetic properties. Our study aimed to explore the underlying mechanisms of gingerol on protecting rats and minks from chemotherapy-induced nausea and vomiting. The preventive impact of gingerol was evaluated in the pica model of rats and the vomiting model of minks induced by cisplatin at every 6 h continuously for a duration of 72 h. Animals were arbitrarily separated into blank control group, simple gingerol control group, cisplatin control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 55 publications
0
31
0
2
Order By: Relevance
“…14 Gingerol, the main pungent component of ginger, is a mixture of various substances, consisting of [6]-gingerol, [8]-gingerol, [10]-gingerol, [6]-shogaol, etc. 15 Qian et al 13,24,25 and Tian et al 26 reported that gingerol has an activity against cisplatin-induced emesis in mink and cisplatin-induced pica in rats by downregulating 5-HT, dopamine (DA) and substance P (SP) expression and regulating the central and peripheral 5-HT, SP, and DA systems.…”
Section: Discussionmentioning
confidence: 99%
“…14 Gingerol, the main pungent component of ginger, is a mixture of various substances, consisting of [6]-gingerol, [8]-gingerol, [10]-gingerol, [6]-shogaol, etc. 15 Qian et al 13,24,25 and Tian et al 26 reported that gingerol has an activity against cisplatin-induced emesis in mink and cisplatin-induced pica in rats by downregulating 5-HT, dopamine (DA) and substance P (SP) expression and regulating the central and peripheral 5-HT, SP, and DA systems.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger root is the rhizome of the Zingiber officinale Roscoe, which usually contains 1–3% oil. The dosage of ginger is usually standardized according to the curcumin content, which is believed to have antibacterial effects [ 10 ], analgesics [ 11 ], antiemetics [ 12 ] and other physiological effects. In Micromedex (an evidence-based clinical reference tool for hospitals and physicians; www.micromedex.com ) ginger is classified as a broad-spectrum antiemetic drug, which can effectively treat nausea and pregnancy-related vomiting and surgery [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemoreceptor trigger zone present in the area postrema allows the chemotactic and other emetic-promoting substances to cross BBB and stimulate the different sections of the DVC [69]. DVC contains various receptors such as D1, D2, 5-HT3, NK1, CB1, and CB2, and these receptors are involved significantly in the induction of emesis [70,71]. Not only CNS but PNS also plays a major role in the etiol- ogy of emesis.…”
Section: Emesis and Cannabismentioning
confidence: 99%